The Effect of Green Accounting, Sustainable Investment, and Environmental Performance on The Value of Manufacturing Companies on The Indonesia Stock Exchange - Rembulan Angger Malasari; Mahameru Rosy Rochmatullah (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2025)
In the modern era, companies are increasingly integrating environmental concerns to enhance their corporate value. This study aims to examine the effect of green accounting, sustainable investment, and environmental performance on the value of manufacturing companies listed on the Indonesia Stock Exchange (IDX) from 2021 to 2023. The study employs a purposive sampling technique, selecting 36 companies that meet the specified criteria. Multiple linear regression analysis is used as the analytical method. The results provide empirical evidence that green accounting and sustainable investment have a significant effect on firm value, whereas environmental performance does not.